EXISTENCE OF HIGH COLLEGE LIBRARY: Optimization of Quality Improvement of Information Services in Order to Meet User Satisfaction in Management Perspective - BAKHTIYAR (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The purpose of the study is to describe the role of higher education libraries in improving the quality of information services to meet the satisfaction of library users. Research's objectivity is to focus on detailed comprehensive studies based on studying content that is very urgent. It is an in-depth investigation of the role of higher education libraries to improve service quality to meet user satisfaction. Given the information needs of the academic community is growing according to the era of the industrial revolution 4.0, where the search for information has been all-digitizing. The research includes in-depth analysis, based on the focus of the study of the role of higher education libraries in improving the quality of information services. Analysis of the research requires realistic critical thinking, for the application of a concept that occurred in the past or the current history, so that it is appropriate to apply the historical approach, characterized by the dominance of critical inquiry into the development of a thought or term. Primary information sources are utilized for primary data. Collecting data utilizes library research, by reading a variety of literature subjecting to the role of higher education libraries, service quality, needs and user satisfaction. The analysis activity is carried out in a qualitative descriptive manner based on the analysis of various kinds of theoretical reading, research and non-research. The research dominates the description and evaluation of factual facts, for the solution of problematic handling in social phenomena, the role of libraries in improving service quality. The validity of the research is realized, by implementing content analysis analysis, it is useful to analyze the meaning of important concepts. Observation of library performance activities, empowered to support the construction of theory. The results of the study are; (1). The type of library service is partially good, having a positive impact on user satisfaction (2). Libraries are required to make optimum efforts to improve service quality so that user satisfaction can be realized. (3). The service is considered satisfactory if it can meet user needs